History of antiphospholipid syndrome - М. Р. Drozhzhina; А. V. Vorobev (IRBIS LLC, 2024)
Here, we discuss hallmark historical events occurred while investigating antiphospholipid syndrome (APS) particularly describing how lupus anticoagulant was discovered and how scientists around the world came to define APS. The prospects for exploring APS at the present time by applying current APS criteria are considered. The contribution of Russian scientists to APS study and catastrophic APS is outlined.